Exploring resilience of Filipino college students with siblings on the autism spectrum: A qualitative approach - Jason Manaois; Franz Dinar Cubillas; Kristoffer Nathan Gaane; Faith Yatoc; April Chanel Varias; Luel Mae Contreras (Academic Journal of Psychology and Counseling, 2026)
Despite the growing attention to autism spectrum disorder (ASD), limited research has explored the lived experiences and resilience of sibling caregivers. This qualitative study explored how Filipino college students with siblings diagnosed with ASD navigate academic, emotional, and familial responsibilities while managing caregiving challenges. Seven participants were purposively selected and engaged in semi-structured interviews using a phenomenological approach to capture their lived experiences and resilience. Findings revealed that resilience is fostered through spirituality, family beliefs, adaptive roles, and emotional communication. Participants reframed their caregiving experiences into meaning-making that shaped personal growth and career goals, and their empathy with others who share similar experiences. Despite enduring emotional burdens and having to make academic sacrifices, they demonstrated emotional maturity, role flexibility, and coping strategies rooted in family connectedness. These insights highlight the complex interplay between caregiving and student development. The study underscores the need for culturally sensitive, family-centered programs that support the mental health and academic struggles of sibling caregivers striving to balance their educational and caregiving duties.